Psychological Analysis in Sterne's Works - Stonys, Juozas (Literatūra, 1969)
Sterne's contribution to the art of psychological analysis in English fiction is considerable. He was more than his contemporaries interested in the inner life of personages. Sterne admitted the inner world of man to be more complicated than it was supposed by his predecessors. He was mostly concerned with psychological contact, i.e. with the psychological interrelations between people when they meet, speak, take glances, act, react etc. This contact is one of the main sources wherefrom the writer takes his material for characterisation. It is not accidental therefore that detailed descriptions of glances, manner of speaking, gestures, motions and other similar external phenomena are of great significance in Sterne's works. In these phenomena Sterne has found large reserves for revealing human psychology. Sterne is also interested in the psychological contact between man and the world of material things. In this world he discovers the reflections of human mind, and in many a case his descriptions of material things become a means of characterisation.Sterne's works present an early stage of the art of psychological analysis.
Keywords: -